RELATION OF NURSE TIME RESPONSES IN PROVIDING SERVICES WITH CLIENT SATISFACTION IN EDUCATIONAL GIRLS SAMPANG - Amir, Faisal (NHM PRESS, 2085)
Client satisfaction is determined by the service which one of them is the response time(response time) is fast and proper handling. The result of preliminary study in get 10 familyof patient that response time at IGD RSUD Sampang â‰¥ 5 (five) minute not according toservice standard. The purpose of this study is to see the description of the relationshipbetween the response time nurses in providing services with client satisfaction in IGDRSUD Sampang. The type of research used in this study is cross sectional with the independent variableresponse time and the dependent variable of client satisfaction. The study population was1260 patients and the samples were 93 respondents. The sampling technique used is nonsampality sampling samples indencental sampling. The results obtained in p value 0,000 â‰¤ Î± 0.05 then H0 in rejected Ha in receipt. It isknown that there is a relationship of response time with patient satisfaction. Should nurseIGD to improve the quality of professionalism in serving. Hospital management shouldprovide a 24-hour clinic so that the case of true emergency and false emergency can beseparated. The availability of human resources and the means of pre-facilities as they affectthe speed of service. Should know that the quality of service nurses either responsiveness, empthy,reliability, and assurance can make client satisfaction in the eri maintained at a high level.